(untitled) (Economic and Political Thought, 2024)
In the context of the growing need to finance pro‑social activities, social bonds are emerging as a promising tool for raising capital that can serve both public and private interests. This article aims to assess the potential of social bonds as a mechanism for financing social initiatives. Through a literature review, analysis of empirical data on the value of issuing social bonds and case studies, the main benefits and challenges of issuing these financial instruments are identified. A distinction is also made between social bonds and social impact bonds. The case studies involved the European Commission’s issuance of bonds from the SURE program and social impact bonds issued by New York City (known as Rikers Island SIBs).